Coloring Artemis graphs - Lévêque, Benjamin; Maffray, Frédéric; Reed, Bruce; Trotignon, Nicolas (Theoretical computer science, 2009)
We consider the class of graphs that contain no odd hole, no antihole, and no “prism” (a graph consisting of two disjoint triangles with three disjoint paths between them). We give an algorithm that can optimally color the vertices of these graphs in time O ( n 2 m ) .